From speech to legal commitment: the democracy of Brazilian public education management regularized from the National Education Plan 2014-2024 (Olhar de Professor, 2023)
Thesis Summary.
Keywords: School administration; Democratic administration.; Educational Legislation; Educational Planning.; Educational Policies.